Fragile-X–Associated Tremor/Ataxia Syndrome (FXTAS) in Females with the FMR1 Premutation - Hagerman, R.J.; Leavitt, B.R.; Farzin, F.; Jacquemont, S.; Greco, C.M.; Brunberg, J.A.; Tassone, F.; Hessl, D.; Harris, S.W.; Zhang, L.; Jardini, T.; Gane, L.W.; et al. (American journal of human genetics, 2004)
We describe five female carriers of the FMR1 premutation who presented with symptoms of tremor and ataxia and who received a diagnosis of definite or probable fragile-X–associated tremor/ataxia syndrome (FXTAS). Unlike their male counterparts with FXTAS, none of the women had dementia. Females had not been reported in previous studies of FXTAS, suggesting that they may be relatively protected from this disorder. Brain tissue was available from one of the five subjects, a women who died at age 85 years; microscopic examination revealed intranuclear neuronal and astrocytic inclusions, in accord with the findings previously reported in males with FXTAS. The work-up of families with the FMR1 mutation should include questions regarding neurological symptoms in both older male and female carriers, with the expectation that females may also manifest the symptoms of FXTAS, although more subtly and less often than their male counterparts.